The Politics of Immigration: Introduction to a Special Issue on US Immigration - Jonathon W. Moses (European Journal of American Studies)
In reading this special issue we gain a remarkably insightful glimpse of the important role that immigration policy has played, and will continue to play, in several important aspects of contemporary American life.  After eight years of the Bush Administration, a new immigration policy is poised to rise again from the ashes of the infamous Sensenbrenner Bill.1  A fresh political and economic context ensures this.